Edukasi “Pilpil“, Pilah dan Pilih Sampah di SD Negeri 2 Kelusa, Kecamatan Payangan, Kabupaten Gianyar - I Komang Bayu Tista Yoga (Jurnal Pengabdian Kepada Masyarakat, 2025)
Waste is a big problem that is often faced in schools. The situation becomes worse because students do not know much about waste and how to process it. They also don't have many supporting facilities. Therefore, it is important for students to learn how to sort waste and avoid throwing waste carelessly. Starting from this problem, this community service initiative aims to provide a solution by informing people about the importance of maintaining cleanliness, managing and sorting organic and inorganic waste and using it to make compost. In practice, this initiative helps provide segregated waste bins. This service activity is carried out through a process of socialization, licensing, preparation, implementation and evaluation. As a result of this service activity, students better understand the importance of maintaining cleanliness, better understand how to sort waste independently, and better understand the benefits. Apart from that, SDN 2 Kelusa students learned about the benefits of 3R waste processing, which means reduce, use and return.